1998
DOI: 10.3354/meps165293
|View full text |Cite
|
Sign up to set email alerts
|

Rapid phlorotannin induction and relaxation in five Washington kelps

Abstract: ABSTRACT-Wounding of both terrestrial and marine plants is known to induce chemical responses in the plants; the induced compounds may defend against herbivory or act in wound-healing processes. We demonstrate here, for the first time, induction of phlorotannins in kelps (Phaeophyta, Laminariales). an important and widespread group of marine benthic algae. The rapid response of kelps to mechanical wounding contrasts with previously published work on other marine algae, where response has been slower. In 4 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 51 publications
3
65
0
1
Order By: Relevance
“…The investigators suggested that the compounds responsible for this induced resistance were probably not phlorotannins because phlorotannin concentrations are very low in S. filipendula and levels of phlorotannins do not relate to feeding by this herbivore. 106 ' 155 Induced defenses in macroalgae usually occur over a period of days 145 to weeks 144 > 155 following damage. The production of activated defenses (wound-induced biotransformation) 156 is an alternative way that herbivores can influence the potency of chemical defenses in algae.…”
Section: Macroalgaementioning
confidence: 99%
“…The investigators suggested that the compounds responsible for this induced resistance were probably not phlorotannins because phlorotannin concentrations are very low in S. filipendula and levels of phlorotannins do not relate to feeding by this herbivore. 106 ' 155 Induced defenses in macroalgae usually occur over a period of days 145 to weeks 144 > 155 following damage. The production of activated defenses (wound-induced biotransformation) 156 is an alternative way that herbivores can influence the potency of chemical defenses in algae.…”
Section: Macroalgaementioning
confidence: 99%
“…Thus, the timing of defence induction and relaxation are essential elements in the balance of costs and benefits of defences (e.g. Karban & Myers 1989;Adler & Harvell 1990;Hammerstrom et al 1998;Underwood 1998;Young & Okello 1998;Raimondi et al 2000;Zangerl 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition the pilot study showed that grazed pieces of C. platylobium were more preferred than non-grazed pieces (t = À2.97, df = 4, P = 0.04), suggesting an inducible response and we assumed that this alga-grazer combination would be suitable for testing the indirect induction mediated by waterborne cues, as attack by a macrograzer would have a higher impact on the algae and could trigger the release of waterborne cues. Duration of the treatment phase for the screening and multi-treatment experiments was in the range of induction times found in the literature (Hammerstrom et al 1998;Toth and Pavia 2000).…”
Section: Treatment Phasementioning
confidence: 98%
“…Six days later, 0.1 g of each algal piece was submerged in 4 ml of 80% methanol for 48 h in total darkness in order to extract polyphenols. To determine the concentration of polyphenols per gram, we used the Folin-Ciocalteu (Sigma) assay (Waterman and Mole 1994;Van Alstyne 1995;Hammerstrom et al 1998) and compared this with a phloroglucinol standard, which was used to calculate the calibration slope (Waterman and Mole 1994). We added 5 ml of the reagent Folin-Ciocalteu to 0.18 ml of the polyphenol extract.…”
Section: Polyphenol Analysis In Galaxaura Diessingianamentioning
confidence: 99%
See 1 more Smart Citation